(untitled) (Experimental biology, 2009)
It was studied the influence of seeds priming by biologically active preparations from biohumus on functional activity of superoxidedismutase and peroxdase in leaves and roots of 10-days sprouts of maize with the Bolivian type of the cytoplasmic male sterility, which grown up at various concentration NaCl.